Hydrogen Materials Science and Chemistry of Metal Hydrides - Hampton, Michael D.; Schur, Dmitry V.; Zaginaichenko, Svetlana Yu; Trefilov, V. I. (Springer Netherlands, 2002)
In September, 1999, with the generous support of NATO, scientists from 18 different nations gathered in Katsiveli, Yalta, Ukraine at the NATO Advanced Research Workshop on Hydrogen Materials Science and Chemistry of Metal Hydrides to present their research and to discuss world energy problems and possible solutions, interactions of hydrogen with materials, the role of hydrogen in materials science, and the chemistry of metal hydrides. High level and highly professional presentations were accompanied by a great deal of discussion and debate of the issues from both fundamental and global perspectives. The result was a large number of new collaborations, new directions, and better understanding of energy and materials issues. The research presented at this meeting can be found in this volume. These papers range from global perspectives such as the new vision of energy and how hydrogen fits into that future, to reviews such as a look at nickel hydride over the last 40 years, to very specific current research. A large number of papers are included on hydrogen and materials. These papers include articles on properties such as superconductivity, diffusion EMF, magnetic properties, physico chemical properties, phase composition, and permeability as a result of the interaction with or incorporation of hydrogen. Also included are papers discussing the use of hydrogen as a processing or alloying agent. The use of hydrogen in the synthesis of battery electrode materials, composite materials, and alloys is also presented
Keywords: Engineering; Renewable and Green Energy; Metallic Materials; Characterization and Evaluation of Materials; Social Sciences, general; Renewable energy resources; Renewable energy sources; Alternate energy sources; Green energy industries; Social sciences; Metals; Materials science; Konferenzschrift